Marital Rape Crisis: Lessons Learnt from the Survivors’ Perspectives and Experiences - Chauraya, Efiritha (Journal of Gender Related Studies, 2025)
Purpose: One area that has received scanty reporting worldwide and in developing countries particularly, is ‘marital rape’. Marital rape is the fastest growing violent crime in developing countries, yet it is one of the least studied phenomena. Zimbabwe is not spared of this phenomenon. The few country studies carried out on the phenomenon have pointed to the need for effective remediation. The focus of this study is on this call. In coming up with an informed remediation, this study started with an understanding of the survivors’ experiences and perspectives so as to unpack the intricacies surrounding marital rape. Methodology: The study adopted a qualitative methodology in order to gain depth and detail in the phenomenon. A sample of 24 women, all formally employed, participated in the study. Face to face semi-structured interviews extracted the women’s experiences and perspectives of marital rape. Interviews were semi-structured so as not to be restricted to specific questions and the questions could also be rephrased. Face to face interviews had an added advantage of gaining nuances of the participants’ answers, which would have been lost had the interviews been telephonic or email. All the participants had confirmed cases of marital rape. Data were collected and analysed concurrently. The issue under study was highly sensitive and it is for this reason that ethical considerations were undertaken to protect and serve the participants, as their being and safety was of primary concern Thematic analysis was employed in data analysis, and what was most important was to recognize what was important in the data and give it meaning. Findings: Data disclosed that marital rape was devastating to the survivors as the wives registered hostile bedroom climates. The wives had convergent opinions and experiences of marital rape as a patriarchal ideology and a tactic by their husbands to uphold masculinity. Reporting of marital rape was undermined by an atmosphere of societal ridicule, blame, shaming and stigmatisation, highly attributable to culture and socialisation. Unique Contribution to Theory, Practice and Policy: Different from other studies, this study proposes a comprehensive ‘think and change’ intervention as the most viable and effective route to rid the Zimbabwe community of the menace. The ‘think and change’ intervention shifts attention from the survivor solely to the abuser, abused, and social support networks.